Beyond Cognition: Experts’ Views on Affective-Motivational Research Dispositions in the Social Sciences - Wessels, Insa; Rueß, Julia; Jenßen, Lars; Gess, Christopher; Deicke, Wolfgang (Frontiers in Psychology, 2018)
Research competence as a key ability of students in the social sciences has thus far been conceptualized as consisting primarily of mainly cognitive dispositions. However, due toowing to its highly complex and demanding nature, competence in conducting research might require additional affective and motivational dispositions. To address this deficiency in the literature, first, we conducted a qualitative interview study with academic experts (N = 16) in which we asked them to identify challenging research situations and the affective-motivational research dispositions needed to cope with them. We employed a subsequent online rating (N = 27) to evaluate the identified critical research situations and dispositions needed to cope with thesethat had been identified. The resulting affective-motivational facet of research competence encompasses 6 challenging situations that are often encountered and 9 dispositions that are necessary for to pursuing successfully conduct research in the social sciences and may be used to both inform and evaluate research-based learning. The interview-based approach may serve as an exemplary procedure to postulate affective-motivational facets of competence models.